Comparing nuclear trajectories in Germany and the United Kingdom: From regimes to democracies in sociotechnical transitions and discontinuities. (January 2020) - Johnstone, Phil; Stirling, Andy
Abstract: This paper focuses on the starkly differing nuclear policies of Germany and the UK. Germany has committed to discontinue nuclear power, aiming to phase the technology out by 2022. The UK has long professed the aim of a 'nuclear renaissance', promoting the most ambitious nuclear construction programme in Europe. The present analysis of this contrast is based around a simple yet fundamental question: which aspects contribute most to producing such divergent energy developments in these two countries? Distinguishing possible interpretive dimensions that are relatively 'internal' or 'external' to the main foci of attention in sociotechnical transitions theory, we develop a novel set of criteria spanning technical, economic, resource-based and political issues. Under each, we ask whether specific characteristics of either national setting would tend to make the phase out of nuclear power more or less likely. Our findings are that 'internal' aspects tend to predict discontinuity to be more likely in the UK than Germany. Only 'external' aspects clearly predict the actual trend. We argue on this basis that sociotechnical discontinuity is rather poorly explained by reference to the circumscribed concepts highlighted in conventional narrow versions of transitions theory. What is evidently more important, are wider political factors relating broadly to general 'qualities of democracy'.